Whole-genome resequencing reveals aberrant autosomal SNPs affect chicken feathering rate. Issue 5 (3rd October 2022) - Qiu, Mohan; Yang, Chaowu; Du, Huarui; Li, Qingyun; Zhang, Zengrong; Xiong, Xia; Yu, Chunlin; Song, Xiaoyan; Hu, Chenming; Xia, Bo; Yang, Li; Peng, Han; et al.
Abstract: Previous studies have shown that the feather growth rate of chicks is determined by two alleles located on the sex chromosome Z; however, in chicken production, feathering is usually not consistently controlled by the sex chromosome. To identify whether the feathering rate is related to autosomal inheritance, whole-genome resequencing was performed in eight chickens with slow- and fast-feathering rate. A total of 54, 984 autosomal single nucleotide polymorphisms (SNPs) were identified, including 393 and 376 exonic SNPs in slow-feathering and fast-feathering chickens, respectively. Mutated genes were mainly involved in response to stimuli and growth and reproduction processes. Mutated genes related to slow-feathering rate were mainly involved in wingless-type MMTV integration site signaling pathway and mitogen-activated protein kinase signaling pathway, whereas mutated genes associated with fast-feathering rate were primarily enriched in autophagy, calcium signaling pathway, extracellular matrix-receptor interaction, and Focal adhesion processes. Importantly, two SNPs, involved in feather development, were found in the exonic regions of Wnt signaling genes. These results shed new light on the relationship between genetic mutation and feather growth rate from the perspective of autosomal inheritance and may have economic significance in chicken breeding.